Analyzing a successful incubator business model: The case of Barcelona Activa (2014)
Successful business incubators have a critical role in the development of local, regional, and national economies through the creation of jobs and the generation of profits, technology development, and innovations. Business incubators are recent and popular organizational forms that are created, often with the help of economic development agencies, to support and accelerate the development and success of affiliated ventures. The chapter examines Barcelona Activa as a successful business incubator in Catalonia (Spain), analyzing the incubator's supply and demand for products and services from the resource-based view approach. Empirically, the chapter is based on qualitative methodology analyzing in depth the case of Barcelona Activa. The findings of the study show that the incubator model's adjustments between the supply and demand of products and services generated are the main reason for the low mortality rate of new firms and the substantial increase in incubators' turnover. This research has important implications for both researchers and government agencies. © 2014 Springer Science+Business Media New York. All rights are reserved.